2015
DOI: 10.2147/ijn.s95483
|View full text |Cite
|
Sign up to set email alerts
|

Novel green synthesis of gold nanoparticles using Citrullus lanatus rind and investigation of proteasome inhibitory activity, antibacterial, and antioxidant potential

Abstract: Biological synthesis of nanoparticles using nontoxic, eco-friendly approaches is gaining importance owing to their fascinating biocompatibility and environmentally benign nature. This study describes the green synthesis approach for synthesis of gold nanoparticles (ANPs) using aqueous extract of the rind of watermelon as a fruit waste and evaluate its biopotential in terms of proteasome inhibitory activity, antibacterial, and antioxidant potential. The synthesized ANPs were characterized using UV–vis spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(18 citation statements)
references
References 65 publications
1
16
0
1
Order By: Relevance
“…As described previously in the study by Patra et al [35], AC-AgNPs nitric oxide radical scavenging potential was confirmed. Concisely, a reaction mixture volume of 200 μL was prepared by mixing 100 μL of AgNPs at various concentrations (20 to100 μg/mL) and 100 μL of 10 mM sodium nitroprusside in phosphate buffer saline (pH 7.4).…”
Section: Methodssupporting
confidence: 78%
“…As described previously in the study by Patra et al [35], AC-AgNPs nitric oxide radical scavenging potential was confirmed. Concisely, a reaction mixture volume of 200 μL was prepared by mixing 100 μL of AgNPs at various concentrations (20 to100 μg/mL) and 100 μL of 10 mM sodium nitroprusside in phosphate buffer saline (pH 7.4).…”
Section: Methodssupporting
confidence: 78%
“…One milligram of the synthesized nanoparticles quenched 53.73% of the oxidant DPPH solution, and its TEAC value was calculated to be 300.91 ± 13.42 μ M Trolox/mg silver nanoparticles. The amount is considered significant when compared with the antioxidant capacities of other nanoparticles and medicinal plants [ 21 , 35 37 ]. El-Rafie and Hamed [ 38 ] reported that Terminalia catappa extract-mediated silver nanoparticles had significant free radical scavenging effect and high antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The mixture of both extracts produced predominantly spherical AuNPs and they had increased antibacterial effects compared with the AuNPs synthesized from the individual plant extract. Patra et al [44] reported the formation of spherical AuNPs with strong antibacterial effects when synergized with rifampicin and kanamycin. Similarly, other researchers confirmed the synthesis of gold nanoparticles using different plant parts such as the stem extract of Cannabis sativa (Indian hemp) [45], fruit extracts of Amomum villosum [46] and leaf and fruit extract of Pistacia atlantica [47].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%